MOTIVASI PETANI DALAM MEMPERTAHANKAN SISTEM TRADISIONAL PADA USAHATANI PADI SAWAH DI DESA PARBAJU JULU KABUPATEN TAPANULI UTARA PROPINSI SUMATERA UTARA - Reflis, Reflis; Nurung, M.; Pratiwi, Juliana Dewi (Jurnal AGRISEP, 2011)
This research aims to identify factors correlated significantly to the motivation of farmers in perseving traditional rainfed farming systems, such as using local seeds and planting once a year.  The population of this study is farmer who still perform the traditional paddy farming system in the Village of North Tapanuli Parbaju Julu County North Sumatra Province. As much as 48 respondents randomly selected from 160 farmers.  A descriptive analyse and Spearman rank correlation are applied in this study.   The study showed that formal education, farmers' perception of the traditional system of rice farming are correlated significantly to farmer motivation in preserving tradional farming system while non-formal education, the traditional system of farming experience, farm size, number of family members are not.  Factors that correlated significantly to farmer motivation in maintaining local seed is non-formal education, farming experience, while the traditional system of formal education, farmers' perception of traditional rice farming system, farm size, number of family members are not correlated significantly.  Furthermore, the number of family members is merely factor that correlated significantly to the farmers motivation in maintaining once a year plantings while others factors are not correlated.